Feedback in reading and disordered eating - Troscianko, E (Oxford University Press, 2017)
Feedback structures are crucial to the act of reading. This is especially clear in contexts for reading where the cognitive stakes are higher, for example, where psychopathology plays a role. Using disordered eating as a test case, this chapter shows how an understanding of the principles of feedback and stability—and in particular the distinction between positive and negative feedback—gives new insights into the psychiatrically relevant causes, experiences, and effects of reading. The evidence comes from existing theoretical and empirical work, and from a pilot study recently conducted in collaboration with the eating disorders charity Beat. By offering a framework for unifying diverse findings on the mechanisms of reading in general and on the cognitive components of specifically literary reading, the chapter makes the case for linking cognitive literary studies, the medical humanities, psychology, and psychiatry with systems and control theory, to theoretical and potentially therapeutic benefit.